Dynamic characterization of structural changes in vapochromic compounds by pair distribution function. (28th February 2017) - Caliandro, R.; Belviso, B. D.; Cuocci, C.; Fuertes, S.; Sicilia, V.; Hanson, J. C.; Tutuncu, G.; Doorhyee, E.; Altomare, A.
Abstract : Two examples of anionic complexes having vapochromic behavior are investigated: [K(H2 O)][Pt( ppy )(CN)2 ] "Pt( ppy )" and [K(H2 O)][Pt( bzq )(CN)2 ] "Pt( bzq )", where ppy = 2-phenylpyridinate and bzq = 7, 8-benzoquinolate. These monohydrate-potassium salts exhibit a change in color from purple to yellow [Pt( ppy )] and from red to yellow [Pt( bzq )] upon heating to 110 °C, and they transform back into the original color upon absorption of water molecules from the environment. Available only in the form of polycrystalline samples, no structural information on such compounds is accessible, due to highly overlapping peaks in powder diffraction profiles. We use in situ Pair Distribution Function measurements on powder samples to investigate the dynamics of the structural changes induced by temperature variations. By means of a multivariate approach, we were able to extract dynamic structural information from collected profiles without using prior knowledge on the static crystal structure of the compounds. The critical temperature and the characteristics of the vapochromic transition have been identified, as well as the main structural changes causing it.